Cultural Identity As Tourism Promotion Strategy In Malioboro Batik Market - Apay Safari*; Nety Novita Hariyani; Eva Desembrianita; Hery Purnomo; Egidius Fkun (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to (1) determine the existence of batik as a cultural identity in tourism promotion in the Malioboro area and (2) determine the effectiveness of cultural identity as a Yogyakarta batik tourism promotion strategy. This research is qualitative research with descriptive methods. This study describes cultural identity as a batik tourism promotion strategy in Yogyakarta. Data collection was carried out using observation, documentation, and literature search techniques. The data analysis method used is Miles and Huberman's perspective method, namely data presentation, data reduction, and conclusion. The results of this study indicate that (1) Hamzah batik which is located in the Malioboro area is one of the largest batik centers strengthens Yogyakarta's identity as a city of culture and (2) Tourism does not always cause a shift or loss of value that threatens the preservation of cultural heritage. 4 main elements influence the success of tourism development at the Malioboro Batik Market, namely tourists, entrepreneurs, local government, and local communities.